Development of an energy management system for palm oil refinery facilities: implementing a systems approach - Febrian, Febrian; Pratoto, Adjar (International Journal of Industrial Optimization, 2025)
This study aims to develop a proactive Energy Management System (EnMS) for a palm oil refinery using a comprehensive systems-based approach implemented carefully during the plant design phase. Unlike conventional methods that rely mainly on historical operational data, this research deliberately utilizes engineering design specifications together with simulation modeling to estimate accurate energy consumption baselines and formulate an ISO 50001-compliant EnMS. A regression-based analysis is systematically applied to define reliable Energy Performance Indicators (EnPIs), using production volume and running hours as key variables influencing overall energy utilization. The resulting analytical model estimates a Specific Energy Consumption (SEC) of 2.168 MWh/MT—significantly higher than the 0.45 MWh/MT BAT benchmark—primarily due to assumptions of full-capacity, simultaneous operation under conservative conditions. To support continuous energy performance improvement, the system incorporates PDCA-based review mechanisms and establishes progressive energy-saving targets: an initial 10% reduction, followed by 1–2% annual incremental improvements. Validation through structured feedback sessions from plant management confirmed the system's strong alignment with operational needs, feasibility within industrial contexts, and readiness for phased implementation. Ultimately, this study contributes a novel, simulation-based framework for integrating EnMS during the design stage, offering a scalable and adaptable model for energy-intensive industries that aim to enhance efficiency and achieve long-term sustainability from the outset.